The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1080/03014467800002871
|View full text |Cite
|
Sign up to set email alerts
|

Growth of schoolchildren with early, average and late ages of peak height velocity

Abstract: A sample of Swedish urban schoolchildren (357 girls, 373 boys) born in 1954/55 followed from 10 to 18 years were grouped according to peak height velocity age (PHV age) into early, average and late maturers. Mean heights differed between the maturity groups at ages from 10.0 to 14.0 years for girls and 10.5 to 17.0 years for boys. Mean weights differed between the maturity groups at all ages up to 16.0 years for girls and up to 18.0 years for boys. The earlier the maturity process, the heavier for given height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
41
1
6

Year Published

1978
1978
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 19 publications
12
41
1
6
Order By: Relevance
“…Thus, MPV during adolescence decreases gradually as the timing of MPV becomes later. Such tendency was also shown by Lindgren (1978), among others, who showed significant differences in respective mean velocities at PHV in early, average, and late maturers. (1-4) There exists a function (t) ʰ V 0 such that { (t − k) : k ʰ z} is an orthogonal basis of V 0 .…”
supporting
confidence: 58%
“…Thus, MPV during adolescence decreases gradually as the timing of MPV becomes later. Such tendency was also shown by Lindgren (1978), among others, who showed significant differences in respective mean velocities at PHV in early, average, and late maturers. (1-4) There exists a function (t) ʰ V 0 such that { (t − k) : k ʰ z} is an orthogonal basis of V 0 .…”
supporting
confidence: 58%
“…28,33 Longitudinal data on growth of Swedish schoolchildren showed that increased body weight was associated with earlier peak height velocity in both genders. 34 The gain of 1 unit of BMI between 2 and 8 years of age was associated with an average of 0.11 years earlier for peak height velocity. 35 There are only few studies, which have investigated the hormonal regulation of the acceleration of bone age in obese children.…”
Section: Growthmentioning
confidence: 96%
“…[77][78][79][80][81][82][83][84] Similar findings are observed in boys as measured by growth spurt or genital and pubic hair maturation. 81,[85][86][87] Body size measures also have been associated with early puberty, 82,86,88 as have dietary and physical activity exposures and pubertal timing. 79,[89][90][91][92][93][94] Environmental exposure to persistent halogenated organic chemicals such as PCBs, dichlorodiphenyltrichloroethane/dichlorodiphenyldichloroethylene (DDT/DDE), and brominated flame retardants have been associated with pubertal alterations, as have dioxin, hexachlorobenzene (HCB), endosulfan, and heavy metals, but to a lesser extent ( Table 2).…”
Section: Human Studiesmentioning
confidence: 99%